Religious Plurality in the Madiun Residency After the Administrative Modernization of the 20th Century - Mochammad Nginwanun Likullil Mahamid (JUSPI (Jurnal Sejarah Peradaban Islam), 2022)
This article aims to answer the question of how indigenous officials in the Madiun Residency responded to the attitude of the Dutch East Indies Government which was anti to religious issues, given its position as part of the administrative area of the Dutch East Indies Government formed after the Java War (1825-1830), in addition to controlling the colonies, there were also efforts to separate religion and government, thus making indigenous peoples struggled in carrying out their worship and religious activities until the end of the 19th century. Using historical methods and approaches to the sociology of religion, as well as reinforced by the Challenge and Response theory, which was initiated by Arnold Joseph Tonybee, the findings show that there was interference from the priyayi elite and peasants who urged the Dutch government to issue a policy of administrative modernization in the 20th century, which provided an opportunity for indigenous officials to hold certain posts in the government,  then the native officials responded again dengan gave a kind of flexibility in carrying out religious activities for every religious believer.